A Multicultural Counseling Approach To Encourage The Development Of Youth With Culture - yiying yiying; Silvia Netri; Zaidi Fadzil; Lilis Satriah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Multicultural counseling is an important approach in guiding adolescent development that takes into account cultural diversity. Culture as a whole system of ideas, actions and results of human work, plays a central role in adolescent development. This research aims to find out how a multicultural counseling approach can encourage the development of adolescents with culture. The research method used is a literature review study. However, this literature review study summarizes the understanding of multicultural counseling, adolescent development, and the role of culture in the context of this development. The results show that a multicultural counseling approach is not just a method, but also a deep philosophy that embraces cultural diversity to guide adolescents toward sustainable emotional, social, and psychological maturity. In conclusion, the integration of a multicultural counseling approach not only supports teenagers in responding to cultural diversity, but also forms individuals who are more tolerant, inclusive and ready to face an increasingly complex world.